2011
DOI: 10.1007/s00417-011-1636-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of flexible ranibizumab treatment in age-related macular degeneration and search for parameters with impact on outcome

Abstract: CFT is a sensitive and early predictor of VA deterioration. Four letters of acute VA loss seems to be a critical limit. VA loss of ≥ 4 letters appears to be associated with incomplete recovery. Eyes with <1 line of gain at the end of the loading phase should be considered for continuation of treatment at months 3 and 4. According to our calculations an average number of 8.4 injections/eye seems to be necessary to maintain stabilization of vision in the first year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 21 publications
(62 reference statements)
4
32
0
4
Order By: Relevance
“…Although substantial differences in efficacy could be seen compared to the clinical trials, the results from other observational studies on ranibizumab efficacy were in general similar to the current study (Dadgostar et al 2009;Rothenbuehler et al 2009;Querques et al 2010;Rotsos et al 2010;Gerding et al 2011;Gupta et al 2011;Cohen et al 2013;Finger et al 2013;Lala et al 2013;Rakic et al 2013;Wolf & Kampik 2014). Considering the treatment patterns, an apparent increase in long-term visual acuity was found in patients who completed the loading phase compared to a decrease in visual acuity in those who did not.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although substantial differences in efficacy could be seen compared to the clinical trials, the results from other observational studies on ranibizumab efficacy were in general similar to the current study (Dadgostar et al 2009;Rothenbuehler et al 2009;Querques et al 2010;Rotsos et al 2010;Gerding et al 2011;Gupta et al 2011;Cohen et al 2013;Finger et al 2013;Lala et al 2013;Rakic et al 2013;Wolf & Kampik 2014). Considering the treatment patterns, an apparent increase in long-term visual acuity was found in patients who completed the loading phase compared to a decrease in visual acuity in those who did not.…”
Section: Discussionsupporting
confidence: 83%
“…Observational studies located in several European countries have been conducted to evaluate the efficacy of ranibizumab for neovascular AMD in clinical practice in their respective countries (Dadgostar et al 2009;Rothenbuehler et al 2009;Querques et al 2010;Rotsos et al 2010;Gerding et al 2011;Gupta et al 2011;Cohen et al 2013;Finger et al 2013;Lala et al 2013;Rakic et al 2013;Wolf & Kampik 2014). Following marketing approval of ranibizumab for neovascular AMD, the Dutch Health Authority had requested an observational study to assess the effectiveness and safety of ranibizumab in daily clinical practice in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Although p.r.n. regimens often have been associated with secondary functional losses after the loading dose [17][18][19], it has been shown that strict monthly visits and sensitive retreatment criteria may achieve good and durable functional results [8,20,21]. Our mean of 7.5 injections during the 12 months p.r.n.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The recent study that compared pro re nata dosing strategies with monthly ranibizumab showed similar outcomes but the outcomes in real-life does not always mirror the clinical trial results. 3,4 Although the treating ophthalmologists are satisfied by a five-lettergain in vision, most patients struggle to read well while the others are unable to cope with more complex activities in their daily life.…”
Section: Introductionmentioning
confidence: 99%